Capturing and Keeping Student Engagement in Marketing [Webinar] - Hatton-Jones, Siobhan; Tombleson, Bridget; Rundle-Thiele, Sharyn (John WIley & Sons Australia Ltd., 2020)
At the height of the pandemic, you probably received a lot of general advice on how to improve the online learning experience. However, many marketing lecturers told us that discipline-specific guidance has been harder to find. In a world where we are competing against the likes of TikTok for students’ attention, how do you keep them focused and engaged with their education? It is a big question and a common challenge for the ANZ higher education community. A challenge which has only be exasperated by the COVID-19 shutdown and the remote learning environment that might be here to stay. Capturing & Keeping Student Engagement in Marketing is a virtual seminar where leading marketing academics share their best practices for engaging marketing students – both online and in the classroom. Meet the presenters: Siobhan Hatton-Jones (Curtin University): Securing student engagement with a 5-pillar teaching approach Bridget Tombleson (Curtin University): Leveraging industry experience to spark the interest of students and exploring the impact of transmedia learning during COVID-19 Sharyn Rundle-Thiele (Griffith University): Using experiential design to encourage deep-learning via authentic assessment and reflective practice